Study on the Shear Capacity of the Wet Joint of the Prefabricated Bridge Panel with a Special-Shaped Shear Key - Fan Feng; Fanglin Huang; De Zhou; Weibin Wen; Yong Tao (Advances in Civil Engineering)
Steel-concrete composite beam has been widely applied in civil engineering, and the concrete during operation may crack due to the large shear force at the wet joint. A new concrete panel shear key with the boss is designed to strengthen the shear capacity of the wet joint part. Three different configurations of specimens are tested to study the shear capacity of the wet joint. These specimens include plain concrete specimens with shear keys, specimens with reinforcement and no shear key, and specimens with both shear keys and reinforcements. An experimental study is designed and conducted to verify the shear capacity of each specimen. The experimental results show that the ultimate shear capacity of the new wet joint structure is 73% higher than the conventional one. Meanwhile, the shear capacity of the new wet joint structure is theoretically predicted, and the finite element models are established to demonstrate the effectiveness of the experiment and the good performance of the new wet joint design.